2011
DOI: 10.1080/09540121.2011.608795
|View full text |Cite
|
Sign up to set email alerts
|

Under-reporting of alcohol and substance use versus other psychiatric symptoms in individuals living with HIV

Abstract: Substance use is known to negatively impact outcomes in patients living with HIV by decreasing adherence to and effectiveness of antiretroviral therapies. Alcohol and other drug abuse and dependence are widespread among HIV-positive individuals, though reported rates vary greatly by study, suggesting the possibility of under-reporting. The extent to which patients minimize symptoms and the factors that influence reporting remain to be determined. The present study sought to gauge the degree to which substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…Under-reporting is common in populations where drinking is prohibited, among HIV-infected patients (Bilal et al, 1990, Hormes et al, 2012), and in SSA (Michalak and Trocki, 2009). New HIV patients are especially likely to under-report drinking in fear of being denied ART (Sorsdahl et al, 2012, Papas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Under-reporting is common in populations where drinking is prohibited, among HIV-infected patients (Bilal et al, 1990, Hormes et al, 2012), and in SSA (Michalak and Trocki, 2009). New HIV patients are especially likely to under-report drinking in fear of being denied ART (Sorsdahl et al, 2012, Papas et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…44, 45 Underreporting of alcohol use by patients, particularly in response to perceived stigmatization and pressure by clinicians, has been reported. 46 Where treatment decisions are linked to the demonstration of abstinence, as in consideration for hepatitis C treatment, underreporting may be more common. 47 The challenges in performing an effective assessment of alcohol use are compounded by the lack of time available in most clinical encounters to address these challenging issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although under-reporting of substance use has been documented for adults with HIV (Hormes et al, 2012), few studies have reported validity of substance use self-report in an adolescent population with HIV. Murphy and colleagues (2000), in a study of high-risk youth age 13–20 both with and without HIV, used ACASI to query participants regarding the timing of their last marijuana use and compared their self-report with urine cannabinoid testing, about which participants had been informed in advance.…”
Section: Introductionmentioning
confidence: 99%